2020
DOI: 10.3390/min10100845
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Efficiencies of Locally Available Neutralizing Agents for Passive Treatment of Acid Mine Drainage

Abstract: Acid mine drainage (AMD) generated from the mining industry elevates environmental concerns due to the pollution and contamination it causes to bodies of water. Over the years, passive treatment of AMD using alkalinity-generating materials have been widely studied with pH neutralization as its commonly observed mechanism. During the treatment process, heavy metal removal is also promoted by precipitation due to pH change or through adsorption facilitated by the mineral component of the materials. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…In the tests it was observed that the concrete aggregate showed efficiency in the treatment, which resulted in the removal of 99% iron, 99% nickel, 96% aluminum and 57% sulfates. In addition, the concrete aggregate was evaluated, which resulted in the removal of 94% iron, 78% nickel, 92% aluminum and 28% sulfate [32].…”
Section: G Results Of the Decrease Of The Metallic Content During The...mentioning
confidence: 99%
“…In the tests it was observed that the concrete aggregate showed efficiency in the treatment, which resulted in the removal of 99% iron, 99% nickel, 96% aluminum and 57% sulfates. In addition, the concrete aggregate was evaluated, which resulted in the removal of 94% iron, 78% nickel, 92% aluminum and 28% sulfate [32].…”
Section: G Results Of the Decrease Of The Metallic Content During The...mentioning
confidence: 99%
“…In this study, more of the smaller sand particles were composed of calcite, as discussed in more detail in Section 3.3. This may also be beneficial in terms of dissolution kinetics because the overall reaction surface area is larger with smaller particles [10].…”
Section: Calcite Dissolution In Raw Sand and Fractionated Sand: Colum...mentioning
confidence: 99%
“…Operational results from a pilot horizontal flow system as well as a more advanced vertical flow system with a novel hydraulic design have shown that the systems are also effective in neutralizing acidic WWW while increasing the sodium adsorption ratio (SAR) of the effluent [8,9]. The neutralization mechanism has been attributed to abiotic dissolution of calcite present in the sand [8,9] and may be applicable to other forms of acidic WW, similar to passive systems for treatment of acid mine drainage [10,11].…”
Section: Introductionmentioning
confidence: 99%